2020
DOI: 10.1021/acs.jpca.9b10149
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Eigen Can Induce Proton Transfer at a Hydrophobic–Hydrophilic Interface

Abstract: The investigation of proton localization at a hydrophobic− hydrophilic interface is an important problem in chemical and materials sciences. In this study, protonated benzene (i.e., benzenium ion) and water clusters [BZH + W n (where n = 1−6)] are selected as prototype models to understand the interfacial interactions and proton transfer mechanism between a carbonaceous surface and water molecules. The excess protons can localize in the vicinity of the hydrophobic−hydrophilic interface, and these clusters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…For Bz-H + W 3 , we find nevertheless a cluster where the water molecule interacts with the π-cloud of Bz instead of H 3 O + interacting with this π-cloud as suggested earlier by Duncan and co-workers. As discussed by Maiyelvaganan et al, [21] the cluster found by Duncan and co-workers is less stable than the one we give here by ~6 kcal/mol as established at the CCSD(T)/CBS level. In the following we will consider the most stable one as displayed in Figure 2.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations
“…For Bz-H + W 3 , we find nevertheless a cluster where the water molecule interacts with the π-cloud of Bz instead of H 3 O + interacting with this π-cloud as suggested earlier by Duncan and co-workers. As discussed by Maiyelvaganan et al, [21] the cluster found by Duncan and co-workers is less stable than the one we give here by ~6 kcal/mol as established at the CCSD(T)/CBS level. In the following we will consider the most stable one as displayed in Figure 2.…”
Section: Resultscontrasting
confidence: 48%
“…[10][11][12][13][14][15] Among them, H-bonding and charge induced interactions in protonated water clusters are ubiquitous in nature. [16][17][18][19][20][21] Nevertheless, the experimental determination of the structure and the stability of such complexes is very difficult and still challenging. [22] Instead, advanced computational techniques can provide reliable qualitative and quantitative insights on the structure, the rotational, vibrational, and electronic spectra of these molecular complexes, complementary to experimental works.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the most concerned proton transfer processes, the excited-state intramolecular proton transfer (ESIPT), can present a series of unique photochemical properties through the significant phototautomerizations induced by the excitation-strengthened hydrogen bond. It has been demonstrated that the synergistic effect of ESIPT and TICT could further efficiently stabilize the torsional configuration by reducing the molecule energy accompanied by the dissociation of the π conjugation and nearly complete charge transfer between two fragments connecting the rotation bond, thus further ensuring the preferential and efficient charge-transfer and separation. This distinct characteristic of the ESIPT triggered TICT process has been typically investigated in a series of functionalized organic materials, such as photostable fluorophores, photosensitizers, and aggregation induced emission luminogens (AIEgens). For instance, by regulating the polarity of the solvent, the planar local excited state of the benzotriazole based ultraviolet absorber could be preferentially stabilized by generating a highly polar twisted charger transfer state through ESIPT triggered TICT process, resulting in the enhancement of the photostability of the ultraviolet absorbers . However, although it has been extensively studied on the final ESIPT triggered TICT on simple fluorescent molecules, such as coumarin, benzotriazole, benzimidazole, and benzophenones, it is still a challenging task to extend this strategy in the π-conjugated heterocycling molecules consisting of multiple proton acceptors, which is of crucial significance in promoting the performance of semiconductive organic materials.…”
Section: Introductionmentioning
confidence: 99%